2021
DOI: 10.1002/pbc.29341
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of chromosomal abnormalities at relapse in children with relapsed acute myeloid leukemia: A retrospective cohort study of the Relapsed AML 2001/01 Study

Abstract: Background In addition to treatment response, cytogenetic and molecular aberrations are the most important prognostic factors in children with de novo acute myeloid leukemia (AML). However, little is known about cytogenetics at the time of relapse. Methods This international study analyzed the prognostic value of cytogenetic profiles and karyotypic changes in pediatric relapsed AML in relation to the probability of event‐free (pEFS) and overall survival (pOS). For this purpose, cytogenetic reports from all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
2
2
0
1
Order By: Relevance
“…In our study, the favourable cytogenetic group had an OS of 86% (CI95% [63; 100]), which includes CBF AML, compared to 51% in the intermediate group and 0% in the high-risk group. This benefit in terms of survival in function of cytogenetic risk group has also been shown at relapse in the study of Klein et al 28 but also in the Kasper et al study concerning the in the CBF AML subgroup. 11 The safety profile of the reinduction regimen in our study was deemed acceptable without toxic death directly attributable to reinduction therapy and only one allergic reaction linked to GO infusion.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In our study, the favourable cytogenetic group had an OS of 86% (CI95% [63; 100]), which includes CBF AML, compared to 51% in the intermediate group and 0% in the high-risk group. This benefit in terms of survival in function of cytogenetic risk group has also been shown at relapse in the study of Klein et al 28 but also in the Kasper et al study concerning the in the CBF AML subgroup. 11 The safety profile of the reinduction regimen in our study was deemed acceptable without toxic death directly attributable to reinduction therapy and only one allergic reaction linked to GO infusion.…”
Section: Discussionsupporting
confidence: 57%
“…In our study, the favourable cytogenetic group had an OS of 86% (CI95% [63; 100]), which includes CBF AML, compared to 51% in the intermediate group and 0% in the high‐risk group. This benefit in terms of survival in function of cytogenetic risk group has also been shown at relapse in the study of Klein et al 28 but also in the Kasper et al study concerning the in the CBF AML subgroup 11 …”
Section: Discussionsupporting
confidence: 52%
“…In our study, cytogenetic and molecular aberrations remained the most powerful predictors for childhood AML prognosis. Previous publications reported similar prognostic significance with ‐7/del(7q) and ‐5/del(5q) carrying the poorest prognosis 18,19 . Hasle et al 20 reported HSCT could not prolong the survival of patients with monosomy 7 or del(7).…”
Section: Discussionmentioning
confidence: 74%
“…Previous publications reported similar prognostic significance with -7/del(7q) and -5/del(5q) carrying the poorest prognosis. 18,19 Hasle et al 20 reported HSCT could not prolong the survival of patients with monosomy 7 or del (7). More effective therapies are warranted for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Прогноз при рецидиве ОМЛ существенно лучше при так называемых CBF-лейкозах (t(8;21)(q22;q22.1)/ RUNX1::RUNX1T1 и inv(16)(p13.1q22)/CBFβ::MYH11) [6]. Существенное значение имеет длительность интервала от достижения ПР1 до возникновения рецидива: при раннем рецидиве (в первые 12 месяцев после достижения ПР1) вероятность достижения второй ремиссии (ПР2) составляет около 50 %, а 5-летняя общая выживаемость (ОВ) -10-15 %; в то время как при позднем рецидиве ( 1 года после достижения ПР1) -75 и 37 % соответственно.…”
Section: Introductionunclassified